Smart management and irrigation demand monitoring in Cyprus, using remote sensing and water resources simulation and optimization - Papadavid, George; Michaelides, Silas; Hadjimitsis, Diofantos G. (My University, 2011)
This paper presents a research project which integrates technological tools for developing a complete system for monitoring and determining irrigation demand on a systematic basis in Cyprus. Such tools are multi-spectral remotely sensed data dynamic water budget simulation and optimization, crop evapotranspiration (ETc) models and microsensor technology. The main aim is to estimate ETc in Cyprus and, furthermore, to undertake the required measures for an effective irrigation water management in the future. Evapotranspiration is difficult to determine since it combines various meteorological and field parameters while in literature quite many different models for estimating ETc are put forward. The proposed wireless sensor network acts as a monitoring tool for providing measurements of the necessary parameters: meteorological, climatic data and other auxiliary parameters required by the irrigation model in order to determine the irrigation demand. Reflectance is determined directly from satellite images. Finally, using the WaterWare irrigation software, irrigation scheduling is planned for the area of interest in Paphos, Cyprus. This area is located at almost sea level and is characterized by mild micro-climate. The results of the paper refer to year 2009 and show the daily water requirements of the specific crop in study.
Keywords: Evapotranspiration; Environmental Software & Services GmbH; Energy balance; Evaporative fraction